AB0642 Validation of a disease-specific health – related quality of life measure for italian adult patients with systemic lupus erythematosus: Lupusqol-italy. (23rd January 2014) - Perricone, C.; Ceccarelli, F.; Bartosiewicz, I.; Pacucci, V.; Conti, V.; Massaro, L.; Miranda, F.; Truglia, S.; Alessandri, C.; Spinelli, F.R.; Valesini, G.; Conti, F.
Abstract : Background: As recommended by the European League Against Rheumatism (EULAR), assessment of SLE patients should include not only the evaluation of disease activity and chronic damage, but also of quality of life (QoL). Several non-specific health related (HR) QoL instruments, such as the short form (SF)-36, have been applied in patients affected by SLE, demonstrating an impaired QoL compared with healthy subjects. Recently, a specific questionnaire to evaluate QoL in adult SLE patients (LupusQoL) has been developed and validated in United Kingdom (UK) and in Northern American SLE populations. Objectives: To assess the validity of a modified version of LupusQoL adapted for italian patients (Lupus-QoL-Italy) in adult Italian SLE patients. Methods: The LupusQoL-Italy was administered to a cohort of Italian patients affected with SLE consecutively followed. At each visit, clinical and laboratory data were collected. Disease activity was assessed with SLEDAI-2K, while chronic damage was measured with SLICC. To perform a control, QoL was evaluated also with SF-36. The Italian version of LupusQoL questionnaire was developed by the University of Central Lancashire and the East Lancashire Hospitals NHS Trust (www.lupusqol.com ), after a linguistic validation process. The LupusQoL-Italy consists in 34-items included in eight domains: physical health (8 items), pain (3 items), planning (3 items), intimate relationships (2 items), burden to others (3 items), emotional health (6 items), body image (5 items), and fatigue (4 items), each scored with a 5-point Likert response scale. Item response scores were totalled for each domain and the mean raw domain score was obtained by dividing the total score by the number of items in that domain. The mean raw domain score was transformed to scores ranging from 0 (worst HRQOL) to 100 (best HRQOL) by dividing by 4 (the number of Likert responses [5 responses] minus 1) and then multiplying by 100. Results: Eighty-six Italian SLE patients were enrolled in the study (M/F 11/75, mean age 41.0±12.1 years, mean disease duration 123.6±94.6 months; mean SLEDAI 1.5±2.3; mean SLICC 0.2±0.6). The LupusQoL-Italy demonstrated substantial evidence of construct validity. Indeed, each domain showed good correlation when compared with equivalent domains of the SF-36 (P<0.001 for all comparisons). LupusQoL-Italy discriminated between patients with different degrees of disease activity according to SLEDAI: Lupus-QoL domains showed a trend to lower values in patients with higher disease activity (SLEDAI-2K≥4) compared with those with lower disease activity (SLEDAI<4), reaching statistically significant difference when considering the domains "burden to others", "emotional health" and "body image" (P=0.03, P=0.03 and P=0.01, respectively). Conclusions: We validated for the first time a modified SLE-specific QoL instrument adapted for usage in adult Italian patients affected by SLE. Disclosure of Interest: None Declared